VALIDITAS PEMERIKSAAN KADAR HEMOGLOBIN MENGGUNAKAN METODE HB METER PADA REMAJA PUTRI DI MAN WONOSARI - Hidayat, Noor; Sunarti, Sunarti (Universitas Ahmad Dahlan, 2015)
AbstractBackground: Anemia is still a nutritional problem in worldwide, especially in developing countries. Anemia is a medical condition which the number of red blood cells or hemoglobin less than 12 gram/100ml. Determination to know anemia can be performed by laboratory test for examine the levels of hemoglobin. The level of hemoglobin test is one of the routine blood tests are needed to diagnose a disease. Many methods are used for examine hemoglobin levels, including methods tallquist, sahli, kupersulfat and cyanmethemoglobine. There is more practical hemoglobin levels test tool which used Hb meter. Gold standard used for checking hemoglobin levels are cyanmethemoglobine method.Method: This research was a descriptive study which used laboratory test. The samples in this research were teenage girl class III in MAN Wonosari.Result: The sensitivity velues is based on the results was 45.45%, while the specificity values was 64.61%. False positive values was 35.58%, while the false negative velue was 54.54%.Conclusion: Sensitivity and specificity velues on this research this showed had result is not good Keyword: Hb meter, sensitivity, anemia, teenage girl, specificity